The EU budgetary package 2021 to 2027 almost finalised: An assessment - Thomas Reininger (The Vienna Institute for International Economic Studies (wiiw), 2021)
This policy note presents an assessment of the EU budgetary package for 2021-2027, including the European Union Recovery Instrument 'Next Generation EU' (EURI-NGEU), with an introduction to the EU decision-making process and the state of play of the relevant legislation as well as an annexed overview of (a) revenue-side decisions, (b) the size, composition and allocation of expenditures and (c) the new rule-of-law regulation. Major achievements are complementary common EU borrowing for EURI-NGEU programmes and the increased focus on climate. However, the EU budget remains tiny, and a national fiscal and (common) monetary policy is needed for stabilisation. EURI-NGEU grants, which are particularly relevant for member states with below-average per-capita income, primarily target public investment in structural change aimed at climate-related and digitisation projects, but they may also help to finance COVID-induced national fiscal deficits, albeit only to a small extent. Governance will be the main challenge facing the implementation of these projects. Compared with the Commission's proposal, the European Council cut funding for EU-wide strategic investments and for external action (neighbourhood, development, humanitarian aid), and, thus, the funds for external action even decline relative to 2014-2020 (EU27) in the midst of a global pandemic. Cuts to the proposed climate-specific Just Transition Fund undermine the 30% climate spending target, which also hinges on how direct agricultural payments are classified. Progress on the revenue side with the new plastic packaging wastebased national contribution and the roadmap to further new own resources contrasts with the expanded privilege of rebate on the GNI-based contribution for a few member states.
Keywords: E61; E62; F55; H50; H60; H61; 330; European Union; Budget; Government expenditure; Policy design and consistency; Policy coordination; International Institutional Arrangements